The effect of daily religious fasting on tear film characteristics and ocular surface - Ibrahim, Wan Nur Farhana; Che Azemin, Mohd Zulfaezal (IIUM Press, International Islamic University Malaysia, 2018)
Introduction: Religious fasting is an act of refraining oneself from eating and drinking beginning at dawn until sunset. The changes in meal time and long period of meal constraint may influence the tear quality and ocular surface. Objective: The purpose of this study was to investigate the effect of daily religious fasting on tear film characteristics and ocular surface integrity. Methodology: This is a prospective study involving 29 eyes from 29 healthy participants. The tear film characteristics were assessed by measuring the non-invasive tear break-up time (NITBUT), tear meniscus height (TMH) and total tear secretion, and fluorescein ocular surface staining method was used to determine the ocular surface integrity. The measurements were performed in the morning (8.00 to 10.00 a.m.) and evening (4.00 to 6.00 p.m.) during each non-fasting and fasting periods. Results: The results showed no statistically significant difference noted for all parameters measured in the morning when comparison was made between non-fasting and fasting periods. Conversely, in the evening, NITBUT value was significantly lower during fasting period, (p = 0.001), but, TMH, total tear secretion and ocular surface staining revealed no significant differences between non-fasting and fasting periods. Conclusion: Our study revealed that daily religious fasting only significantly reduced the NITBUT value in the evening which possibly due to dehydration; however, it did not affect TMH, total tear secretion and ocular surface integrity. The absence of fluid loading at pre-dawn meal could be the reason of non-noticeable differences noted in the morning.